POTENTIAL GROWTH INHIBITION ACTIVITY OF FECAL MATERIALS, MUCUS AND CULTURED WATER OF TILAPIA OREOCHROMIS NILOTICUS ON ACUTE HEPATOPANCREATIC NECROSIS DISEASE (AHPND) - CAUSING PATHOGEN VIBRIO PARAHAEMOLYTICUS - Phuong Thanh, Le Ngoc; Co, Ho Hai; Truc Ly, Trinh Thi; Tung, Hoang; Hong Hanh, Bui Thi (Vietnam Journal of Biotechnology, 2018)
Shrimp farming plays a key role in economy of many countries all over the world. Unfortunately, a disease called Acute Hepatopancreatic Necrosis Disease (AHPND) or Early Mortality Syndrome (EMS) caused by Vibrio parahaemolyticus spreading from Asia to Central America costs shrimp industry billions of dollars annually. In the past few years, scientists from multi-disciplinary field collaborated to find out a solution for this disease. Until now, there are not any effective approaches to prevent and cure this disease. However, co-culturing shrimp with tilapia was carried out to limit the outbreak of AHPND in farm scale in many countries. Some previous studies also mentioned the benefits of this farming method to prevent other pathogens. The aim of this research is to determine whether intrinsic factors or cultured water of tilapia play role in inhibition of V. parahaemolyticus – pathogen causing AHPND. These factors include: mucus on tilapia gill and skin, tilapia fecal material, and microbiota or dissolved chemicals in culturing of tilapia. Anti-V. parahaemolyticus activity of tilapia (Oreochromis niloticus) fresh and overnight incubated feces and mucus were tested using agar well diffusion method. The effectiveness of feces and mucus inhibition was not clear, both of samples generated a weak inhibition on V. parahaemolyticus. Determination of V. parahaemolyticus inhibiting factor of tilapia cultured water using challenge test showed that dissolved compounds (smaller than 0.22 µm) inhibited the growth of V. parahaemolyticus. The presence of these compounds in tilapia-cultured water reduced V. parahaemolyticus to 17 times lower than that of the negative control with the seawater alone within the first three hours post challenge.